Pathways to the Professoriate: Women Midlife Career Changers A Literature Review of Prior Career Experts to New Career Novices - Catherine A. Cherrstrom (Adult Education Research Conference, 2014)
The purpose of the study is to investigate the career transitions and strategies of women midlife career changers to the professoriate. As part of the study, the purpose of this paper is to discuss a completed literature review of adult transitions from prior career expert to new career novice.